COVER AND PREFACE JURNAL KONVERSI ENERGI DAN MANUFAKTUR VOL. 8 NO. 2 (2023) - Jurnal Konversi Energi dan Manufaktur Editor's (Jurnal Konversi Energi dan Manufaktur, 2023)
Firmansyah et al., in their paper, conducted local stress analysis using finite element-based software. The study is carried out on the static load that comes from the ship when it is anchored at the harbour. This analysis aims to determine the fender's stress characteristics and maximum stress value. Yuniadi and Kurniawan, in their paper, analyzed the strength and safety factor of the chassis using the finite element method to determine the safety factor in the chassis design that was made. Darmawan and Kurniawan, in their paper, determine the wear rate of the brake pad so that the prediction of the service life of the brake pad is known and the factors causing the difference in the wear rate of the brake pad installed on the trailer bogies and motor bogies. Yulianti et al., in their paper, discuss the hydrogen output monitoring system on Fuel Cell Electric Vehicles (FCEV) using the Node-RED software application and regarding flowmeters with RS 232 output. Syaka et al., in their paper, add injectors that aim to improve fuel delivery fuel at high speed, which is expected to boost the power and torque of the standard vehicle. The vehicle used is a motorcycle with a programmed fuel injection (PGM-FI) system for the fuel atomizer. Sugiyanto et al., in their paper, varied the heating temperature and hydraulic pressure on the box and gear moulds using an injection moulding process to produce the maximum mould shape for the box and gear shapes. Basori et al., in their paper, designed a storage rack capable of accommodating and holding a load of gas cylinders and their contents and can be mobilized at a certain height.